Investigation of surface degradation of binderless particleboards (BPB) by utilizing rattan furniture waste materials - Halim, Zahurin; Ahmad, Zuraida; Sharif, Safian; Kalam, Anizah (2017)
Binderless particleboards (BPB) are decent alternative of green products, yet the degradation behavior during and after their service-life is rarely focused by the researchers in this area. This study aims to investigate degradation mechanisms of BPB by utilizing rattan furniture waste (RFW), produced via hot-pressing (HP) technique. These BPB, treated BPB and conventional boards were subjected to room condition (RC), natural weathering (NW) and soil burial (SB) degradation for six months. The BPB in their service-life had similar environment as in RC, where the boards were slightly swelled due to bare surfaces that absorbed surrounding moisture. The similar environment after BPB’s service-life were as NW and SB, where those boards almost 90% degraded with occurrences of surface cracks, fungi growth, eroded and peeled of sample surfaces. The treated BPB required slightly longer time to degrade compared to control BPB, attributable to better inter-bonding between fibers. The pine wood and wood-plastic-composite (WPC) experienced about 55%-70% of degradation rate, owing to highly resistance to fungal microbial attack and plastic existing inside wood for WPC. The degradation mechanisms were combination of scission and cross-linking of fiber, fungal attack and rate of moisture absorption in BPB. The data obtained assist in enlightening BPBs' planning service-life as well as maintenance cost and waste landfill management.